The Role of Early Adoption of Artificial Intelligence in Supporting the Growth of Micro and Ultra-Micro Enterprises in Indonesia: Challenges and Opportunities - Fajri, Fajri; Perdana, Kukuh Adi; Manurung, Dita Ully; Narayan Dharmawan, Putu Kana; Dewi, Nurma Gupita (Jurnal Akuntansi dan Bisnis, 2024)
The rapid advancement of Artificial Intelligence (AI) technologies has unlocked significant potential for enhancing the performance of micro and ultra-micro enterprises (UMEs) in Indonesia. This study explores the role of early AI adoption in supporting the growth and competitiveness of these enterprises, which constitute a vital segment of Indonesia’s economy. The paper examines how AI-driven tools can improve business operations, from marketing automation and customer engagement to inventory management and financial planning. Moreover, it discusses the unique challenges faced by micro and ultra-micro enterprises in adopting AI, including limited digital literacy, financial constraints, and inadequate infrastructure. Opportunities arising from AI adoption, such as improved access to markets, personalized customer experiences, and data-driven decision-making, are also highlighted. The findings emphasize the importance of tailored AI solutions, government support, and capacity-building initiatives to address the barriers to adoption. This paper concludes by offering actionable recommendations for policymakers, technology providers, and entrepreneurs to foster an enabling ecosystem for AI integration, thereby unlocking its full potential to drive sustainable growth and innovation in the sector.Keywords: Artificial Intelligence, Early Adoption, Micro Enterprises, Ultra-Micro Enterprises, Business Growth, Digital Transformation,